(untitled) (Global Conference on Medical and Health Sciences, 2026)
In 19th century France, women were considered as second class citizens in society. They were deprived of the opportunity to gain independence, preserve their wealth and determine their own destiny. Honoré de Balzac, who lived and worked during this period, depicted the real picture of French society in his novels of the “Human Comedy” series, and also artistically interpreted the struggle of women to gain power and control in their lives. In this article, through the analysis of female characters in Balzac’s novel, the specific features of the fate of women in bourgeois society are revealed.